PROSPEK PENGEMBANGAN AGRIBISNIS DALAM MEWUJUDKAN KETAHANAN PANGAN - Sumastuti, Efriyani (Semarang State University, 2011)
Agribusiness sector has an important role in the process of economic development. The contribution of this sector in economic development, areto increase the food production for domestic consumption, become the largest provider of employment, enlarge the market for industries, increase the supply of money for saving and increase the income. Up to now, the role of the agricultural sector in Indonesia is sogreatin supporting the food fullfillmentand providing an employment for farm house holds. The great role and potency of agribusiness sector in realizing the food sustainability still have to face many challenges and complex issues. There should be many efforts for the existance of agribusiness sector. This study will discuss the agribussiness potency, prospects, problems and the efforts that should be done for the food sustainability.Sektor agribisnis mempunyai peranan penting dalam proses pembangunan ekonomi. Kontribusi sektor ini dalam pembangunan ekonomi antara lain meningkatkan produksi pangan untuk konsumsi domestik, sebagai penyedia tenaga kerja terbesar, memperbesar pasar untuk industri, meningkatkan supply uang tabungan dan meningkatkan devisa. Sampai saat ini, peranan sektor pertanian di Indonesia begitu besar dalam mendukung pemenuhan pangan dan memberikan lapangan kerja bagi rumah tangga petani. Peran dan potensi sektor agribisnis yang demikian besar dalam mewujudkan ketahanan pangan di masa yang akan datang masih harus menghadapi berbagai tantangan dan permasalahan kompleks. Untuk itu perlu dilakukan upaya-upaya untuk tetap eksis. Studi ini akan membahas tentang potensi, prospek, permasalahan serta upaya yang perlu dilakukan sektor agribisnis dalam mewujudkan ketahanan pangan.